Background illumination enhanced photo-stimulated up-conversion emission in persistent luminescent SrAl2O4:(Eu2+, Dy3+). Issue 9 (November 2015) - Ji, Zhenguo; Bao, Wenhao; Mao, Qinan; Xi, Junhua; Kong, Zhe; Zhang, Jun
Abstract: Persistent luminescent SrAl2 O4 :(Eu 2+, Dy 3+ ) ceramics were prepared by electron beam bombardment and their photo-stimulated up-conversion property was investigated. It is found that the intensity of photo-stimulated up-conversion emission of SrAl2 O4 :(Eu 2+, Dy 3+ ) decays in the same way as that of the persistent luminescence under the continuous or pulsed excitation at 980 nm, while stable and enhanced photo stimulated up-conversion emission is observed with the background illumination of 475 nm light. A possible model is proposed to illustrate the enhanced photo stimulated up-conversion emission assisted by background illumination. Based on that model, the band gap of SrAl2 O4 :(Eu 2+, Dy 3+ ) is calculated from the excitation spectrum.